Ethics and Professionalism Challenges in Digital Learning Practices in Medical Faculty: An Evidence-Based Case Review - Kurniawan, Kayla Ashila; Nabila Ripalga, Denia Putri; Primanagara, Risnandya (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2026)
Implementation of Digital learning in medical education is challenging. Since Professionalism and Professional Identity is a core competency, implementing Digital technology including Virtual Reality (VR) and Artificial Intelligence (AI) can intervene development of Professionalism Identity. This Evidence Based Case Review aims to find the impact of implementations Digital Technology in medical students through various implementation in the medical curriculum. The research indicates that the developmental patterns of professionalism among students remain varied. While the use of VR and AI is perceived to achieve the desired educational impact, their implementation triggers significant ethical and professional concerns, such as data privacy, secondary skills achievements, and professional integrity. The integration of technology in medical education needs ethical considerations within the curriculum to ensure that technological advancements do not affect medical professionalism.